2015
DOI: 10.1007/s12274-015-0809-8
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced spatially indirect exciton recombination in zinc-blende/wurtzite CdS heterostructures

Abstract: Strain engineering provides an effective mean of tuning the fundamental properties of semiconductors for electric and optoelectronic applications. Here we report on how the applied strain changes the emission properties of heterostructures consisting of different crystalline phases in the same CdS nanobelts. The strained portion was found to produce an additional emission peak on the low-energy side that was blueshifted with increasing strain. Furthermore, the additional emission peak obeyed the Varshni equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 53 publications
4
5
0
Order By: Relevance
“…As the size of the tetragonal inclusions is extremely small, the large blueshift of P 1 emission peak and saturation of P 1 intensity can be observed. This sort of blueshift of emission peaks has been commonly observed in quantum wells and other confined heterostructures 47 48 . Increasing the temperature to 140 K, similar trend was observed except that the blueshift of P 1 becomes negligibly small, which is probably due to the increasing size of tetragonal inclusions.…”
Section: Resultssupporting
confidence: 63%
“…As the size of the tetragonal inclusions is extremely small, the large blueshift of P 1 emission peak and saturation of P 1 intensity can be observed. This sort of blueshift of emission peaks has been commonly observed in quantum wells and other confined heterostructures 47 48 . Increasing the temperature to 140 K, similar trend was observed except that the blueshift of P 1 becomes negligibly small, which is probably due to the increasing size of tetragonal inclusions.…”
Section: Resultssupporting
confidence: 63%
“…5(b)); this observation indicates the origin of narrow lines to be related to intrinsic energy levels of CdS. The present data is in agreement with previous report by Li et al [39], who have found extra emission peak in PL spectra of CdS nanobelts at 77 K due to strain.…”
Section: (C) Along With the Relative Positions Of Fermi Level In Bulksupporting
confidence: 93%
“…The band gap of ZnO NWs [35] and microwires [36] as well as CdS nanowires/nanotubes [37,38] can be engineered under the influence of strain. In addition to this, strain can also introduce the splitting of exciton emission as demonstrated recently [36,39]. Liao et al [36], report the splitting under the compressive strain while single emission peak is seen under the tensile strain for ZnO microwires.…”
Section: (C) Along With the Relative Positions Of Fermi Level In Bulkmentioning
confidence: 87%
See 1 more Smart Citation
“…But as far as we know, the optical tuning ( e.g. PL, exciton’s dynamics and lasing properties) of NRs by strain-engineering has rarely been investigated before 44 45 . In this work, CdS, of which nanostructures have been widely investigated in their optical properties 46 47 48 49 50 51 , is chosen as the test bed because of its high optical quality and very large fracture strength limit 30 .…”
mentioning
confidence: 99%